Temporomandibular disorders in elderly individuals: the influence of institutionalization and sociodemographic factors - Nélia de Medeiros Sampaio; Mario Cezar Oliveira; Adriana de Oliveira Ortega; Lydia de Brito Santos; Técia Daltro Borges Alves (CoDAS, 2017)
ABSTRACT Purpose The aim of this study was to determine the factors associated with temporomandibular disorders (TMD) in the non-institutionalized and institutionalized elderly population of Feira de Santana, Bahia, Brazil. Methods A cross-sectional study was carried out in 307 subjects over 60 years old of both genders, where 80 are institutionalized and 227 are non-institutionalized. The evaluation of TMD signs and symptoms was performed using the Fonseca Anamnestic Index (IAF) as to sociodemographic, systemic and otological factors. The results were analyzed by correlating the study factors and the prevalence of TMD. A 95% confidence interval (CI) and a 5% significance level were established for all the tests used. Results The results showed that 50.5% of the subjects presented some degree of TMD. The prevalence of TMD was 49.8% among non-institutionalized elderly individuals and of 52.5% among institutionalized individuals. Variation in the prevalence of TMD, with statistical significance according to gender, age, income, tinnitus, dizziness, and depression was observed. Conclusion The prevalence of TMD was significant among the elderly population. There was no statistically significant difference between the prevalence of TMD in institutionalized and non-institutionalized individuals. Identifying TMD in the elderly population may be difficult because the symptoms of these disorders are similar to symptoms commonly presented in some systemic disorders associated with aging.